Attitude and behavioral intention to develop and use MOOCs among academics - Ab Jalil, Habibah; Ma'rof, Aini Marina; Omar, Rosmaria (International Association of Online Engineering, 2019)
Several practice-oriented courses are currently integrated into online learning plat-forms, providing a new wave of instructional approaches among academics. These include the use of Open CourseWare and Massive Open Online Courses (MOOCs). It is worthwhile to explore how learners respond to new teaching methods when practice-oriented courses are placed online. The primary purpose of this study is to determine levels of attitude and behavioural intention to develop and use MOOCs and the possible relationships between those variables. Partici-pants consisted of 238 academics in a Malaysian public university. Descriptive and Pearson Correlation analyses were employed to determine relationships. Re-sults show that: (a) respondents are receptive towards MOOCs as an alternative platform to deliver teaching content; (b) they are mostly ready to develop MOOCs; (c) they are generally prepared to use MOOCs in teaching and learning and (d) there are significant relationships between academic staffs’ attitude and behavioural intention to develop and use MOOCs. The findings of this study are pertinent in understanding MOOCs from the perspective of academics so that proper support can be provided accordingly.